China’s Role In Indonesia's “Crush Malaysia” Campaign - Dahana, A (UI Scholars Hub, 2002)
This paper argues that contrary to the traditionally accepted opinion, the People’s Republic of China (PRC) participated in the Indonesian campaign to crush Malaysia half-heartedly. In fact, despite its strong propaganda broadcast in supporting Indonesia, the PRC was actually a passive participant in the campaign. This is due to the fact that at that time the Chinese supported Malayan Communist Party, which was pursuing a more conciliatory policy toward the Malaysian government. Furthermore, China was probably more concerned with the well-being of ethnic Chinese Malaysia than supporting the local communist party.